The Contexts of Governing Universities in the Former Soviet Countries - Eckel, Peter (International Higher Education, 2024)
From a common Soviet governance approach four different university governance models emerged in former Soviet states after 1991. The models, while interesting in their evolution, might best be considered in light of the operating contexts. Determining governance effectiveness is notoriously challenging, but a contextual understanding through the dual lens of competition and autonomy may help policy makers, university leaders, and academic researchers pursue aligned and appropriate governance structures.